Silversmithing a contemporary guide to making - Hill, Brian; Putland, Andrew (Crowood Press, 2014)
"As well as promoting the traditional origins of handmaking craft skills, this lavish book explains the latest techniques and opportunities that exist for today's designer silversmith. It emphasizes the importance of acquiring fundamental skills as a basis to creating stunning and innovative designs, and illustrates this with fabulous case studies from leading silversmiths."